Kematangan Emosi dan Prososial pada Relawan Desa Lawan COVID-19 ditinjau dari Jenis Kelamin - Aprian Istiono; Mamang Efendy (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
Prosocial behavior and help should be shared by everyone in the face of the COVID-19 pandemic, especially for village volunteers directly involved in providing assistance and assistance in the midst of the COVID-19 pandemic established by the Ministry of Villages PDTT. Prosocial behavior must certainly be owned by village volunteers in carrying out their duties properly. One of the factors that make up prosocial behavior is emotional maturity, emotional maturity plays an important role for volunteers to manage their emotions well in carrying out their duties. The purpose of this study is to find out the relationship between emotional maturity and prosocial behavior as well as differences in emotional maturity and prosocial behavior reviewed from the sexes. The research sample consisted of 72 village volunteers who were randomly selected sampling. Data collection uses emotional maturity scale and self-developed prosocial behavior scale by researchers. Data analysis techniques use simple regression analysis and t-testing. The results showed there was a very significant relationship between emotional maturity and prosocial behavior in village volunteers versus COVID-19. The results also showed no significant differences in prosocial behavior between male volunteers and female volunteers and there was no significant difference in emotional maturity between male volunteers and female volunteers. Which means emotional maturity is an important predictor for prosocial behavior, and prosocial behavior and emotional maturity do not differ between men and women.